Marcas de oralidade em textos multimodais: uma análise do gênero charge - Silva, Edina Aparecida da (2022)
This dissertation aims to analyze orality marks present in writing in multimodal texts. For the analysis, a corpus formed by 14 cartoons that circulate in newspapers, magazines and internet sites was constituted. The analyzed cartoons were selected due to linguistic variations, the resources used to highlight each one, such as gestures, onamatopoeias, that is, the various linguistic and non-linguistic resources used. The textual genres cartoons texts are characterized as multimodal texts, as they present a varied number of resources. Punctuating this issue, we can highlight the concept of orality advocated by Rojo(2009,2013, 2016), Ribeiro(2012) and Kress(1995), whose authors highlight the importance of different texts present in contemporary times. Multimodal texts are widely used to express a certain opinion, position, among others. But, it is necessary to emphasize, mainly, how this type of text can influence a certain reader. Taking this issue into account, it is proposed that the use of language, and in this case oral language, has aroused more and more interest and is therefore the reason for several studies and, therefore, several discussions about it. The occurrence of orality marks of different types, such as those related to conversational markers and linguistic variation in speech, points to the interaction between speech and writing, which are not opposite poles as in the dichotomous view of these two language modalities (MARCUSCHI , 2008). For Marcuschi (2002), Urbano (1995) and Marquesi, Pauliukonis and Elias (2017) the spoken language may present itself in a dialogic manner and may undergo changes according to interactions. In the cartoon genre, we go through the studies of Costa (2020), Marquesi, Pauliukonis and Elias (2017), in which the authors highlight the use of a certain critical content, a certain humor to indicate a political vision, historical context and situations experienced in everyday life . In this sense, the theoretical research was based on authors such as Marcuschi (2001, 2008), Koch and Elias (2006), Rojo (2012), Marquesi, Pauliukonis and Elias (2017), Castilho (2002) and Dionísio (2005). This study indicated that there are oral language traits that signal conversational markers and linguistic variation in the cartoon genre. And, that the reading and understanding of these texts found in the digital environment may change according to the inserted context and in addition to being essential previous, current and advanced knowledge on a given subject.